2015
DOI: 10.1016/j.jsbmb.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cancer stem cells in solid tumors by vitamin D

Abstract: Cancer stem cells (CSCs) are a small subset of cells that may be responsible for initiation, progression and recurrence of tumors. Recent studies have demonstrated that CSCs are highly tumorigenic and resistant to conventional chemotherapies, making them a promising target for the development of preventive/therapeutic agents. A single or combination of various markers, such as CD44, EpCAM, CD49f, CD133, CXCR4, ALDH-1 and CD24, were utilized to isolate CSCs fromvarious types of human cancers. Notch, Hedgehog, W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 104 publications
0
33
0
Order By: Relevance
“…The cancer inhibitory effects of vitamin D compounds, including 1α,25(OH) 2 D 3 and a Gemini vitamin D analog BXL0124, are mediated through signaling pathways involved in cancer stem cell signaling, cell cycle suppression and differentiation pathways (35). TNBC cell lines, such as SUM159, exhibit predominantly patterns of basal cell surface markers with some minor subpopulations of stem-like or luminal type (6).…”
Section: Discussionmentioning
confidence: 99%
“…The cancer inhibitory effects of vitamin D compounds, including 1α,25(OH) 2 D 3 and a Gemini vitamin D analog BXL0124, are mediated through signaling pathways involved in cancer stem cell signaling, cell cycle suppression and differentiation pathways (35). TNBC cell lines, such as SUM159, exhibit predominantly patterns of basal cell surface markers with some minor subpopulations of stem-like or luminal type (6).…”
Section: Discussionmentioning
confidence: 99%
“…They possess the capacity of unlimited self-renewal through symmetric cell division, the ability to give rise to progeny cells through asymmetric division, and an innate resistance to cytotoxic therapeutics 41. Wnt, Notch, Hh, and/or TGF-β signaling pathways are involved in proliferation and maintenance of CSCs, and dysregulation of these pathways might cause the development of CRC 4245. Despite the advancements in diagnosis and targeted and combined treatment, the advanced and metastatic stage of CRC still remains untreatable.…”
Section: Hh Signaling Pathwaymentioning
confidence: 99%
“…We and others have shown that supplementation with dietary vitamin D or treatment with its active hormonal form calcitriol [1,25(OH) 2 D 3 ] exhibits multiple actions to inhibit BCa growth as demonstrated in cultured BCa cells and in lean mouse models of BCa (Deeb, et al 2007; Feldman, et al 2014; Rossdeutscher, et al 2015; Shui and Giovannucci 2014; So and Suh 2015; Welsh 2012). These vitamin D actions include the transcriptional repression of aromatase ( Cyp19 ) (Krishnan, et al 2010; Swami, et al 2011), inhibition of Er expression (Swami, et al 2000; Swami, et al 2013), and suppression of cyclooxygenase-2 (COX-2) expression (Moreno, et al 2005) leading to the reduction in the synthesis of pro-inflammatory mediators such as PGE 2 that are major stimulators of aromatase transcription in BCa (Brown and Simpson 2010; Simpson and Brown 2013a).…”
Section: Introductionmentioning
confidence: 99%